Circulating vitamin D concentrations and risk of breast and prostate cancer: a Mendelian randomization study. (28th December 2018) - Jiang, Xia; Dimou, Niki L; Al-Dabhani, Kawthar; Lewis, Sarah J; Martin, Richard M; Haycock, Philip C; Gunter, Marc J; Key, Timothy J; Eeles, Rosalind A; Muir, Kenneth; Neal, David; Giles, Graham G; et al.
Abstract: Background: Observational studies have suggested an association between circulating vitamin D concentrations [25(OH)D] and risk of breast and prostate cancer, which was not supported by a recent Mendelian randomization (MR) analysis comprising 15 748 breast and 22 898 prostate-cancer cases. Demonstrating causality has proven challenging and one common limitation of MR studies is insufficient power. Methods: We aimed to determine whether circulating concentrations of vitamin D are causally associated with the risk of breast and prostate cancer, by using summary-level data from the largest ever genome-wide association studies conducted on vitamin D ( N  = 73 699), breast cancer ( N case  = 122 977) and prostate cancer ( N case  = 79 148). We constructed a stronger instrument using six common genetic variants (compared with the previous four variants) and applied several two-sample MR methods. Results: We found no evidence to support a causal association between 25(OH)D and risk of breast cancer [OR per 25 nmol/L increase, 1.02 (95% confidence interval: 0.97–1.08), P  = 0.47], oestrogen receptor (ER)+ [1.00 (0.94–1.07), P  = 0.99] or ER− [1.02 (0.90–1.16), P  = 0.75] subsets, prostate cancer [1.00 (0.93–1.07), P  = 0.99] or the advanced subtype [1.02 (0.90–1.16), P  = 0.72] using the inverse-variance-weighted method. Sensitivity analyses did not reveal any sign of directional pleiotropy. Conclusions: Despite its almost five-fold augmented sample size and substantially improved statistical power, our MR analysis does not support a causal effect of circulating 25(OH)D concentrations on breast- or prostate-cancer risk. However, we can still not exclude a modest or non-linear effect of vitamin D. Future studies may be designed to understand the effect of vitamin D in subpopulations with a profound deficiency.